2023
DOI: 10.1136/jech-2023-220760
|View full text |Cite
|
Sign up to set email alerts
|

High levels of high-sensitivity C reactive protein to albumin ratio can increase the risk of cardiovascular disease

Abstract: BackgroundThe high levels of C reactive protein (CRP) to albumin ratio (CAR) is thought to increase the risk of poor outcomes for cancer and cardiovascular disease (CVD). However, the association between CAR and CVD in the Chinese community population has not been investigated.ObjectiveThe aim of this study was to investigate the association between CAR and CVD in the Chinese community population.MethodsA total of 62 067 participants without a history of CVD or cancer were included in this study. Kaplan-Meier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Consistent with our observations, Yang et al. ( 23 ) found that the predictive performance of CAR for cardiovascular disease was better than that of CRP or albumin alone. In addition, our results showed that hemoglobin and eGFR were independently associated with odds of developing OP in patients with PBC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our observations, Yang et al. ( 23 ) found that the predictive performance of CAR for cardiovascular disease was better than that of CRP or albumin alone. In addition, our results showed that hemoglobin and eGFR were independently associated with odds of developing OP in patients with PBC.…”
Section: Discussionsupporting
confidence: 93%
“…The CRP-to-albumin ratio (CAR) is a composite measure and is considered a more useful indicator than either CRP or albumin alone ( 22 ). As an inflammation-based marker, CAR has shown prognostic value in several diseases such as cardiovascular disease, autoimmune disease, and malignancy ( 23 25 ). However, the relationship between the CAR and OP development in patients with PBC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also found that CRP-albumin ratio (CAR) may be an important indicator for predicting cardiovascular risk. [5][6][7][8][9] Our previous studies 10,11 also confirmed that the combined indicator of CRP and albumin played a similar role in evaluating the prognosis of patients with acute myocardial infarction as the Global Registry of Acute Coronary Events (GRACE) score. In addition, platelet-lymphocyte ratio (PLR) was also found to have good predictive value for cardiovascular events.…”
Section: Introductionsupporting
confidence: 58%
“…There have been several studies evaluating the efficacy of the NLR, CAR, and PLR in patients with CAD or COVID-19, and showed that these inflammatory scores have good clinical utility in predicting all-cause mortality in CAD or COVID-19. [4][5][6][7][8][12][13][14][15][16][17] However, few studies evaluated whether these inflammatory scores could effectively predict the prognosis for patients with CAD complicated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A large data set derived from the study of Yang et al indicated the role of high CAR as a risk factor of cardiovascular disease development, even better than CRP or albumin [22]. As for the prognostic value of CAR, recently, Sonsöz et al investigated CAR in acute HF and noticed an increased mortality in the follow-up of the group of patients with high…”
Section: Discussionmentioning
confidence: 99%